A Longitudinal Study Into Indicators of Mental Health, Strengths and Difficulties Reported by Boarding Students as They Transition From Primary School to Secondary Boarding Schools in Perth, Western Australia. Issue 2 (2nd May 2017) - Mander, David J.; Lester, Leanne
Abstract : This study examined indicators of mental health, as well as strengths and difficulties, as reported by same-age boarding and non-boarding students spanning four time points over a 2-year period as they transitioned from primary to boarding school in Western Australia (i.e., at the end of Grade 7, beginning of Grade 8, end of Grade 8, and end of Grade 9). It presents data taken from a larger longitudinal quantitative study, which included 76 male and 74 female boarding students while they were in Grades 7 to 9. Findings indicate that boarding students and non-boarding students reported significant increases in depression, anxiety, as well as emotional symptoms and hyperactivity over time, and reported significant decreases in prosocial behaviour. However, examining the boarder × time interaction, boarding students reported significantly higher levels of anxiety and stress at the end of Grade 8 compared to non-boarding students. No significant difference over time was found in depressive symptomatology between boarding and non-boarding students, whereas at the beginning of Grade 8 and end of Grade 9, boarding students reported significantly higher emotional symptoms than non-boarding students. These findings are discussed in terms of the boarding school context and possible considerations for prevention and practice are presented.